Temperature and burning history affect emissions of greenhouse gases and aerosol particles from tropical peatland fire - Kuwata, Mikinori (2017)
Tropical peatland burning in Asia has been intensifying over the last decades, emitting huge amounts of gas species and aerosol particles. Both laboratory and field studies have been conducted to investigate emission from peat burning, yet a significant variability in data still exists. We conducted a series of experiments to characterize the gas and particulate matter emitted during burning of a peat sample from Sumatra in Indonesia. Heating temperature of peat was found to regulate the ratio of CH4 to CO2 in emissions (ΔCH4/ΔCO2) as well as the chemical composition of particulate matter. The ΔCH4/ΔCO2 ratio was larger for higher temperatures, meaning that CH4 emission is more pronounced at these conditions. Mass spectrometric analysis of organic components indicated that aerosol particles emitted at higher temperatures had more unsaturated bonds and ring structures than that emitted from cooler fires. The result was consistently confirmed by nuclear magnetic resonance analysis. In addition, CH4 emitted by burning charcoal, which is derived from previously burned peat, was lower by at least an order of magnitude than that from fresh peat. These results highlight the importance of both fire history and heating temperature for the composition of tropical peat-fire emissions. They suggest that remote sensing technologies that map fire histories and temperatures could provide improved estimates of emissions.